2018
DOI: 10.1002/cncr.31109
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms predict head and neck cancer survival: Examining plausible behavioral and biological pathways

Abstract: Depressive symptoms at the time of treatment planning predict overall 2-year mortality. Effects are partly influenced by the treatment response. Depression screening and intervention may be beneficial. Future studies should examine parallel biological pathways linking depression to cancer survival, including endocrine disruption and inflammation. Cancer 2018;124:1053-60. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 54 publications
(118 reference statements)
4
95
1
2
Order By: Relevance
“…In addition, we found that, in people with oral cavity and HPV‐negative oropharyngeal and laryngeal cancer, DS were associated with worse survival, while in people with HPV‐positive oropharyngeal cancer, no such association was found. Previous studies on the association between pretreatment DS and overall survival have shown inconsistent results . Two studies in people with different types of HNC found no evidence for such an association (after adjustment), while Shinn et al targeting people with oropharyngeal cancer, Zimmaro et al targeting people with mixed HNC treated with (chemo)radiation, and Chen et al also targeting people with mixed HNC reported an increased risk of earlier death or poorer overall survival among those with pretreatment DS.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In addition, we found that, in people with oral cavity and HPV‐negative oropharyngeal and laryngeal cancer, DS were associated with worse survival, while in people with HPV‐positive oropharyngeal cancer, no such association was found. Previous studies on the association between pretreatment DS and overall survival have shown inconsistent results . Two studies in people with different types of HNC found no evidence for such an association (after adjustment), while Shinn et al targeting people with oropharyngeal cancer, Zimmaro et al targeting people with mixed HNC treated with (chemo)radiation, and Chen et al also targeting people with mixed HNC reported an increased risk of earlier death or poorer overall survival among those with pretreatment DS.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies on the association between pretreatment DS and overall survival have shown inconsistent results . Two studies in people with different types of HNC found no evidence for such an association (after adjustment), while Shinn et al targeting people with oropharyngeal cancer, Zimmaro et al targeting people with mixed HNC treated with (chemo)radiation, and Chen et al also targeting people with mixed HNC reported an increased risk of earlier death or poorer overall survival among those with pretreatment DS. In contrast to our study, Shinn et al did not stratify for HPV status, as HPV status was only available for a subsample.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations